Safety and Mode of Action of Diabetes Medications in comparison with 5-Aminolevulinic Acid (5-ALA) - Peter R. Rehani; Hanaa Iftikhar; Motowo Nakajima; Tohru Tanaka; Zaid Jabbar; Riyadh N. Rehani (Journal of Diabetes Research)
5-Aminolevulinic acid (5-ALA) is a delta amino acid naturally present in every living cell of the human body. 5-ALA is produced in the mitochondria as the first product of the porphyrin synthesis pathway and composes heme; exogenously supplemented 5-ALA helps in upregulating mitochondrial functions. Mitochondrial dysfunction has been associated with the pathophysiology of diabetes mellitus. Thus, in this review, we evaluate the mechanisms of action and adverse effects of common medications used to treat type 2 diabetes mellitus as well as 5-ALA including its mechanism and possible use in diabetes management.